2013 proceedings of the Fifteenth Workshop on Algorithm Engineering and Experiments (ALENEX) - Sanders, Peter 1967-; Zeh, Norbert 1973- (Society for Industrial and Applied Mathematics, SIAM, 2013)
The aim of ALENEX is to provide a forum for the presentation of original research in the design, implementation, and experimental evaluation of algorithms and data structures. Typical submissions will include an extensive experimental analysis of nontrivial algorithmic results, ideally bridging the gap between theory and practice. We also invite submissions that address methodological issues and standards in the experimental evaluation of algorithms and data structures. Some possible areas of applied algorithmic research include but are not limited to databases; networks, including web applications; operations research; and computational problems in the natural sciences or engineering. Submissions are encouraged that address algorithms and data structures for advanced models of computing including memory hierarchies and parallel computing, ranging from instruction parallelism over multicore computing to exascale and cloud computing
Keywords: Computer algorithms; Experiments; Congresses; Software engineering; Experiments; Congresses; Discrete mathematics and graph theory; Konferenzschrift